Can aortic valve calcium score predict a need for permanent pacemaker implantation after transcatheter aortic valve implantation? - Helene Eltchaninoff; Eric Durand; Christophe Tron; Charles Fauvel; Thomas Barbe; Thibaut Hemery; Guillaume Le Pessec; Najime Bouhzam; Nicolas Bettinger; Julie Burdeau; Jade Makke; Quentin Laissac; et al. (Open Heart)
Introduction Conductive disturbances requiring permanent pacemaker (PPM) implantation remain a major concern after transcatheter aortic valve implantation (TAVI).Aims To assess the impact of aortic valve calcium score (AVCS) on conductive disturbances requiring PPM after TAVI.Methods All patients who underwent TAVI with accessible AVCS from the preprocedural CT scan report were included in this retrospective single-centre study. The primary endpoint was the occurrence of a conductive disturbance requiring PPM at 30 days. The association between PPM and AVCS, with its incremental prognostic value, was analysed using multivariable logistic regression, receiver operating characteristic curve analysis and likelihood ratio (LR) test.Results We included 761 patients of which 125 (16%) required PPM at 30 days. AVCS score was significantly higher in patients requiring PPM (3788 (2487–5218) vs 3050 (2043–4367) AU, p<0.001). Using multivariable analysis, preprocedural right bundle branch block (RBBB) (OR 6.61, 95% CI 3.82 to 11.5, p<0.001), first atrioventricular block (OR 1.71, 95% CI 1.03 to 2.83, p=0.037), self-expanding valve (OR 3.25, 95% CI 1.17 to 9.09, p=0.025) and AVCS>4510 AU (OR 1.83, 95% CI 1.04 to 3.20, p=0.035) were independently associated with PPM. AVCS had an incremental discriminative value (C-index 0.79 vs 0.77, LR test p=0.036) over and above traditional PPM risk factors. An algorithm was proposed based on the initial presence of RBBB, AVCS and the type of implanted valve.Conclusion Even if RBBB remained the strongest predictor of PPM post-TAVI, this study suggests that a high AVCS may help identifying patients at increased risk of PPM after TAVI, especially among those without pre-existing RBBB.